Upaya guru Pendidikan Pancasila dalam menumbuhkan karakter peduli lingkungan - Ernawati Ernawati; Bagdawansyah Alqadri; I Nengah Agus Tripayana (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze the efforts of Pancasila Education teachers in fostering environmental care character among students and to identify the supporting and inhibiting factors. The study is motivated by the low level of students’ environmental awareness in maintaining school cleanliness and sustainability. This research employs a qualitative approach with a case study design conducted at SMAS Al-Hamzar Tembeng Putik. The research subjects consist of Pancasila Education teachers, the principal, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed inductively through data reduction, data display, and conclusion drawing. The results indicate that teachers’ efforts are carried out through three main stages: planning, implementation, and evaluation. In the planning stage, environmental care values are integrated into lesson plans and school programs. In the implementation stage, strategies include habituation, teacher role modeling, and students’ involvement in practical environmental activities. Meanwhile, evaluation is conducted through behavioral observation, although it has not yet been fully structured.